Analisis Kemampuan Siswa dalam Menyelesaikan Soal Operasi Hitung Penjumlahan Pecahan Kelas V SDN 23 Pontianak Barat - Wati, Sri Widya; Kartono; Pranata, Rio (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study uses a qualitative approach with a descriptive research type. The study aims to analyze the ability of fifth-grade students of SDN 23 West Pontianak in solving fraction addition problems and identifying difficulties and factors that influence students' abilities in solving these problems. The subjects of the study were fifth-grade students of SDN 23 West Pontianak. Data were collected using test techniques by giving fraction addition problems. The test instrument was used to identify students' abilities in understanding the information in the problems, determining the steps to solve them, and obtaining the correct answers. Data were analyzed descriptively qualitatively through the stages of checking students' answers, grouping students based on their ability levels, identifying the types of errors and difficulties experienced, and interpreting factors that influence students' abilities in solving the problems. The results of the analysis show that students' abilities vary. Students with low abilities have difficulty understanding the information in the problems and are therefore unable to solve the problems well. Students with moderate abilities have been able to understand the contents of the problems, but still have difficulty in determining and applying the steps to solve them. Meanwhile, students with high abilities are able to understand the problems and solve the fraction addition problems well.